2022
DOI: 10.1017/jog.2022.11
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of high-pressure sintering on snow density evolution: experiments and results

Abstract: Very few studies have emphasized the effects of high-pressure sintering on snow density evolution, even though snow as a type of engineering material is widely used in construction engineering in cold regions for snow pavement, snow runway and polar infrastructure. This study presents new experimental results of snow densification under high pressures of up to 100 MPa for a temperature range from −3.5 to −17.3°C and uniaxial compression at the temperature of −10°C and constant strain rates from 5 × 10−4 to 10−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…So, sintering is actually an early stage of the snow metamorphism process [45]. Hong et al ( 2022) conducted an experimental study to observe the change in sintering density during the compression of snow blocks in the temperature range of −100 to 0 degrees and the pressure loading range of 0 to 100 MPa and found that pressure is the most prominent factor affecting sintering density [46]. While considering the increased rate of ice fabrication, low-temperature limits, and the reliable strength of sintered snow, high-pressure sintered snow is conducive to easy, widespread, and efficient utilization as a promising material for construction in polar regions [46].…”
Section: Snow Structural Characteristicsmentioning
confidence: 99%
“…So, sintering is actually an early stage of the snow metamorphism process [45]. Hong et al ( 2022) conducted an experimental study to observe the change in sintering density during the compression of snow blocks in the temperature range of −100 to 0 degrees and the pressure loading range of 0 to 100 MPa and found that pressure is the most prominent factor affecting sintering density [46]. While considering the increased rate of ice fabrication, low-temperature limits, and the reliable strength of sintered snow, high-pressure sintered snow is conducive to easy, widespread, and efficient utilization as a promising material for construction in polar regions [46].…”
Section: Snow Structural Characteristicsmentioning
confidence: 99%